Pelatihan dan Pendampingan Penyusunan Laporan Keuangan Pamdes Di Desa Pandanrejo Oleh Mahasiswa KKN UM - Hadi, Fikri Ichsanul; Puspaningtyas, Miranti (Yayasan Cita Cendikiawan Al Kharizmi, 2023)
Pandanrejo is one of the villages in Wagir District, Malang Regency. The village has abundant natural resources in the form of water. Water in Pandanrejo Village is managed by PAMDes under the auspices of BUMDes Pandanrejo. The problem faced by PAMDes Pandanrejo is the preparation of its financial statements which are not in accordance with applicable accounting standards. This makes it difficult for residents to understand, resulting in distrust of PAMDes Pandanrejo's financial management. This problem encourages the author to carry out community service in the form of training and assistance in preparing financial reports. The method used in developing this program includes six stages, namely problem analysis, making financial report formats, education and socialization, training, mentoring, and evaluation. The result of this service is that the author succeeded in making a format for recording transactions and preparing financial reports in the form of Ms. Excel files which are expected to overcome the problems that exist in PAMDes Pandanrejo.